Facile Growth of Porous Hematite Films for Photoelectrochemical Water Splitting - Shaohua Shen; Jiangang Jiang; Penghui Guo; Liejin Guo (International Journal of Photoenergy)
We introduced a simple fabrication method of porous hematite films with tunable thickness in an aqueous solution containing FeCl3 as the single precursor. We demonstrated that the optimized thickness was necessary for high performance photoelectrochemical water splitting, by balancing photon absorption and charge carrier transport. The highest photocurrent of ca. 0.15 mA cm−2 at 1.0 V versus Ag/AgCl was achieved on the 300 nm thick porous hematite film as photoanode, with IPCE at 370 nm and 0.65 V versus Ag/AgCl to be 9.0%. This simple method allows the facile fabrication of hematite films with porous nanostructure for enabling high photon harvesting efficiency and maximized interfacial charge transfer. These porous hematite films fabricated by this simple solution-based method could be easily modified by metal doping for further enhanced photoelectrochemical activity for water splitting.